INTER-RELIGIOUS RELATIONS IN THE VIEW OF SOCIAL CONSTRUCTIVISM: AN EMPIRICAL STUDY OF SOUTHEAST SULAWESI - Laode Fathun; Vania Zahra Nathania; Tuhfahtu Hasanatul Wahidah (Harmoni, 2025)
This study aims to explore the meanings and strategies underlying the management of interreligious relations, with the goal of fostering collective awareness and harmony within multicultural communities in West Muna Regency, Southeast Sulawesi, Indonesia. Employing an exploratory qualitative approach, data were collected through observation, literature review, and interviews. The findings reveal that the people of West Muna live in a highly multicultural setting, shaped largely by government migration programs that brought Balinese, Javanese, and Bugis communities into the region. This process of assimilation has produced a society characterized by diverse religious, ethnic, and cultural affiliations. Rather than generating division, however, this diversity has fostered harmony and kinship across groups. The community’s shared sense of collective social construction and collective identity strengthens solidarity and pluralist awareness, ultimately shaping West Muna into a cosmopolitan society. Empirical evidence shows that West Muna has experienced no significant social or political conflicts, even during politically sensitive periods. This resilience is rooted in the strong cultural awareness and identity of the Muna people, which serve as guiding principles for intergroup relations and the preservation of social cohesion. AbstrakPenelitian ini bertujuan untuk menjelaskan makna dan strategi dalam pengelolaan hubungan antarumat beragama guna membangun kesadaran kolektif dan harmoni di masyarakat multikultural Kabupaten Muna Barat, Sulawesi Tenggara. Dengan menggunakan pendekatan kualitatif eksploratif, data dikumpulkan melalui observasi, kajian literatur dan wawancara. Hasil penelitian menunjukkan bahwa masyarakat Muna Barat hidup dalam konfigurasi sosial yang sangat multikultural, yang terbentuk terutama melalui program migrasi pemerintah yang menghadirkan komunitas Bali, Jawa, dan Bugis ke wilayah tersebut. Proses asimilasi ini menghasilkan masyarakat dengan keragaman agama, etnis, dan budaya yang luas. Menariknya, keragaman tersebut tidak memicu konflik, tetapi justru memperkuat harmoni, solidaritas, dan ikatan kekerabatan lintas kelompok. Temuan ini menegaskan bahwa konstruksi sosial kolektif dan identitas kolektif masyarakat Muna menjadi fondasi penting dalam menciptakan kesadaran pluralis dan membentuk Muna Barat sebagai masyarakat kosmopolitan. Bukti empiris juga memperlihatkan bahwa hingga kini Muna Barat tidak pernah mengalami konflik sosial maupun politik yang signifikan, bahkan pada periode politik yang sensitif. Ketahanan ini bersumber dari kesadaran budaya dan identitas masyarakat yang kuat, yang berperan sebagai pedoman dalam membangun relasi antar kelompok sekaligus menjaga kohesi sosial. Dengan demikian, studi ini memberikan kontribusi terhadap kajian hubungan antaragama dan praktik moderasi beragama di Indonesia.